Neonatal mortality of sick newborns admitted in a tertiary care teaching hospital in Tamil Nadu, South India - Jeganathan, Sathya; S. A., Rsavikmar; A., Tamilmani; P., Parameshwari P.; Chinnarajalu, Asvatha Valarmathi; Kolkar, Yalaguraswami B. (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal period is an important period in the life where most of the deaths are preventable. In India every year 1 million babies die, which contributes to 25% of the world neonatal mortality. Perinatal death is very high in developing countries including India. Methods: A record based retrospective study was conducted in the Neonatal Intensive care unit(NICU) of Department of Pediatrics, Chengalpattu Medical College in Tamil Nadu, South India. The records were collected for the period of one year from January 2016 to December 2016. All the neonates admitted in the NICU during this period were included in the study. Results: The number of total deliveries in Chengalpattu Medical College for the year 2016 was 9339. Total number of live births was 9170 of which 21.88% were low birth weight and 15.96% were preterm delivery. Mortality rate in males is 3.2% (54/1689) and mortality rate in female is 3.98% (55/1383). The difference in mortality rate among male and female neonates was not significant. Respiratory distress syndrome and prematurity related illness contributed to 45% of the total neonatal deaths (39/110). Birth asphyxia and meconium aspiration contributed to 23.6 % (24/110). Rest of the mortality was contributed by ELBW 11.8% (13/110), major congenital malformation 6.4% (7/110), sepsis 1.8% (2/110) and others. Conclusions: Prematurity related problems and respiratory distress are the leading causes of neonatal mortality and morbidity followed by birth asphyxia in CMCH. Proper identification and management of pre-eclampsia, prevention of preterm and low birth weight deliveries are the need of the hour to reduce the mortality and morbidity among neonates.